Aspergillosis outbreak in an ostrich flock - Timurkaan, N; Keskin, O; Yilmaz, F; Çimtay, I (Polish Soc Veterinary Sciences Editorial Office, 2005)
This study was undertaken to describe clinical, macroscopic, microbiological, and histopathological findings observed in ostriches during an aspergillosis outbreak in a farm. Study material was composed of 12 ostriches in a farm where 53 ostriches were housed in Sanhurfa/Turkey. Clinical symptoms of the sick animals included depression, decreases in feed and water consumption, notable weight loss, severe dyspnoea, open mouth breathing and coughing. When necropsies were conducted on two of the animals, the lungs showed numerous yellowish foci, and contained yellowish-white cheesy material. The walls of the thoracic air sacs were thickened with eosinophilic exudate containing cellular debris and necrotic masses. Aspergillus fumigatus was identified in swabs taken from the lungs and air sacs and plated onto Sabouraud dextrose agars. Histopathologically, granulomatous lesions were observed in the lungs and air sacs. In addition, hyphae of Aspergillus spp. was observed when the tissues were stained with PAS-haematoxyline.
Keywords: ostrich; aspergillosis; pathology